A Concurrent Analysis of Drug Relapse Risk, Drug Avoidance Self-Efficacy, and Aftercare Experiences among Aftercare Program Clients - Malinao, Dennise Mari (Technium Social Sciences Journal, 2024)
The cases of drug use and abuse have predominantly increased globally. This issue has become the most significant challenge among mental health professionals, the national government, and the general population. With the absence of substantial research about drug relapse and avoidance in the Philippines, this mixed-method research seeks to find out the relationship between drug relapse risk and drug avoidance self-efficacy among substance users who participated in the aftercare program. This study employed a concurrent mixed method design, combining both quantitative and qualitative approaches. In the quantitative phase, the Advance Warning of Relapse (AWARE) Questionnaire and Drug Avoidance Self-Efficacy Scale (DASES) were administered to 66 participants from the Aftercare Program (ACP) at the Department of Health Treatment and Rehabilitation Center in Eastern Visayas. The aim was to establish a correlation between the risk of drug relapse and drug avoidance self-efficacy. In the qualitative phase, interviews were conducted with five participants who met the study's inclusion criteria. Purposive sampling was used to select these participants. Quantitative findings revealed that ACP clients had low drug relapse risk and high drug avoidance self-efficacy. Moreover, Pearson product-moment correlation shows an inverse relationship between lower drug relapse risk and high drug avoidance self-efficacy, and vice-versa. However, the correlation between these variables is weak, indicating that drug avoidance self-efficacy is not a strong predictor of relapse risk in aftercare program clients. Similarly, qualitative results exposed the client’s experiences in the After Care Program. Six themes emerge from their experiences, such as their various reasons for taking the drugs, the effects of substance use, their effective coping mechanisms, the treatment of their communities, their accomplishment of recovery goals, and overcoming challenges in their recovery. The study suggests that individuals who participate in the aftercare programs are trying their best to recover and increase their self-efficacy to avoid using drugs. This strong self-efficacy, in combination with various factors such as family support, the acceptance of the community, and continued reminders of the consequences of substance abuse, decreased their vulnerability to use drugs in high-risk situations. The findings will increase the awareness of Filipinos in the prevention and treatment of substance use among their loved ones, relatives, and friends. Likewise, the findings recommend improving the aftercare program to increase its effectiveness and efficiency in preventing relapse among individuals in recovery.